Famous battles of the age of revolution - McNab, Chris, 1970- (McNab, Chris, 1970- Classic warfare., 2018)
Profiles over thirty battles that occurred between American, French, and British forces during the Revolutionary War. Arranged chronologically, each battle features a brief description of the battle including its importance, the dates in which the battle took place, notable leaders, a map showing troop movement on the battlefield, and maps that indicate where the battle took place.